Creative Economy Training on Bossara Lid Making in Kampala Village, Sinjai Timur District: Pelatihan Ekonomi Kreatif Pembuatan Penutup Bosara di Desa Kampala Kecamatan Sinjai Timur - Nurhayani (PADAIDI: Journal of Tourism Dedication, 2024)
Creative economy development is a sustainable option to maintain economic resilience amid the global crisis. The natural economy must be developed because it holds great potential to create a significant economic impact, establish a conducive business environment, and shape a national image and identity based on innovation, creativity, and competitiveness. It also upholds national values and has a positive impact on society. The activity conducted was a training program on the production of bosara covers in Kampala Village. The implementation of this activity consisted of several stages: observation, interviews, and the training phase itself, which included theoretical sessions and practical training on making bosara covers. The target participants for this training were the PKK women’s group and the Majelis Ta'lim. The purpose of this training was to enhance the creativity of the community, enabling them to produce items that could contribute to their economic well-being. The outcome of the training was the creation of bosara covers that can be marketed to meet economic needs. Additionally, participants were able to learn the process of manufacturing bosara covers.